Exploring essential personality traits for professional interpreters: a Delphi method study - Yang, Chunwen (Frontiers in Education, 2025)
IntroductionWith the increasing demand of global communication and rapid advancements in technology, the role of professional interpreters has evolved beyond linguistic competence to include a range of essential personality traits. Despite their critical role in interpreter performance, these traits are underrepresented in empirical research. This study aims to identify and prioritize the key personality traits that contribute to professional interpreter effectiveness using the Delphi method.MethodsA two-round Delphi study was conducted with a purposively selected panel of 20 experts, including interpreter trainers, professionals, and corporate clients. In the first round, open-ended responses were collected to identify essential personality traits, followed by a structured ranking exercise in the second round. Thematic analysis was conducted on qualitative data, and Kendall's W coefficient was applied to measure consensus in the second round using SPSS 26.0.ResultsTwenty experts participated in both rounds. Thematic analysis from round one identified 24 traits, grouped into eight dimensions: Emotional Stability and Resilience (D1), Cognitive Flexibility and Adaptability (D2), Empathy and Cultural Sensitivity (D3), Confidence and Assertiveness (D4), Integrity and Ethical Standards (D5), Self-Motivation and Discipline (D6), Meticulousness (D7), and Patience (D8). In the second round, D2 emerged as the most important trait, followed by D1, D4, D3, D5, D7, D6, D8. Kendall's W = 0.371 (p < 0.001) indicated a significant level of expert consensus.ConclusionThe findings highlight a clear expert consensus on the most essential personality traits required of professional interpreters. These results provide important implications for interpreter training programs, suggesting the need to integrate personality development alongside linguistic and technical skills. Future research should explore trait relevance across specific interpreting modes and settings to refine interpreter competence frameworks further.